2013
DOI: 10.1590/s1679-45082013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Hibernoma cervical e lipoblastomatose

Abstract: Lipoblastoma and lipoblastomatosis are rare benign soft-tissue tumoral lesions resembling fetal adipose tissue. A total of 16 cases of lipoblastoma of the neck were reported in the literature, and only 3 were described in the posterior side of the neck. Hibernoma is a rare benign adipose tumor composed of brown fat cells and only about ten cases occurring in the cervical area have been reported. We reported two rare cases of adipose tissue tumors. The first case was a male infant aged 12 months who had a cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Grossly, these are soft, lobulated and yellow, white or tan in color. Fat, myxoid nodules or cystic spaces separated by fine, white, fibrous septa are seen on cut surface [ 9 , 14 17 , 19 , 21 , 22 , 24 , 27 , 29 ]. All tumors in our study were encapsulated, soft and showed fibrous septations.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Grossly, these are soft, lobulated and yellow, white or tan in color. Fat, myxoid nodules or cystic spaces separated by fine, white, fibrous septa are seen on cut surface [ 9 , 14 17 , 19 , 21 , 22 , 24 , 27 , 29 ]. All tumors in our study were encapsulated, soft and showed fibrous septations.…”
Section: Main Textmentioning
confidence: 99%
“…In one study [ 16 ], lobules bordered by septa were seen in 44%, prominent blood vessels in 76% and myxoid foci in 52% cases. Mitoses are rare, abnormal mitoses are never seen [ 9 , 16 , 17 , 19 21 , 23 , 29 ]. On IHC, adipocytes are positive for CD34 and S100 protein, while primitive cells are positive for Desmin [ 9 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these characteristics can be ambiguous and overlap with other lesions such as simple lipoma, hibernoma, and, importantly, malignant lesions such as myxoid liposarcoma. [ 1 4 8 15 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 8 ] Hibernoma is also characteristic of adults, is very rare in children under 18 years of age, and is histologically defined as a tumor of embryonic brown fat, showing characteristic eosinophilia; also, it usually has a lobular pattern and granular cytoplasm not present in the white fat of lipoblastoma. [ 2 11 15 ] Regardless, both lesions are benign, and the treatment is complete excision. [ 2 8 11 15 ]…”
Section: Discussionmentioning
confidence: 99%